2018
DOI: 10.5194/esurf-2018-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scales of collective entrainment and intermittent transport in collision-driven bed load

Abstract: Abstract. Fluvial bed-load transport is notoriously unpredictable, especially near the threshold of motion where stochastic fluctuations in sediment flux are large. A general statistical mechanics framework has been developed to formally average these fluctuations, and its application requires an intimate understanding of the probabilistic motion of individual particles. Laboratory and field observations suggest that particles are entrained collectively, but this behavior is not well resolved. Collective entra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…One mechanism is the cumulative effect of successive particle‐bed impacts, which causes a fluctuation motion of bed surface particles that makes them more susceptible for entrainment in a continuous rebound state. Note that recent numerical and experimental studies indicate that impact entrainment dominates direct fluid entrainment in turbulent bedload transport (Lee & Jerolmack, ; Pähtz & Durán, ; Vowinckel et al, ). The impact entrainment threshold normalΘte also marks the transition between intermittent and continuous transport. Below normalΘte, turbulent events sustain transport on an intermittent basis, where the intermittency characteristics depend on whether the Shields number Θ is above or below the rebound threshold normalΘtr (Figure ). Sediment transport rate relations like equation are only applicable to steady, continuous transport of nonsuspended sediment (i.e., normalΘnormalΘte) but fail to describe intermittent transport (i.e., normalΘ0.3em<0.3emnormalΘte), which explains why bedload transport formulae like equation fail when normalΘ2normalΘtr (Meyer‐Peter & Müller, ; Recking et al, ) and why one should therefore only use data representing bulk transport when testing such relations (Bunte & Abt, ; Shih & Diplas, ; Singh et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…One mechanism is the cumulative effect of successive particle‐bed impacts, which causes a fluctuation motion of bed surface particles that makes them more susceptible for entrainment in a continuous rebound state. Note that recent numerical and experimental studies indicate that impact entrainment dominates direct fluid entrainment in turbulent bedload transport (Lee & Jerolmack, ; Pähtz & Durán, ; Vowinckel et al, ). The impact entrainment threshold normalΘte also marks the transition between intermittent and continuous transport. Below normalΘte, turbulent events sustain transport on an intermittent basis, where the intermittency characteristics depend on whether the Shields number Θ is above or below the rebound threshold normalΘtr (Figure ). Sediment transport rate relations like equation are only applicable to steady, continuous transport of nonsuspended sediment (i.e., normalΘnormalΘte) but fail to describe intermittent transport (i.e., normalΘ0.3em<0.3emnormalΘte), which explains why bedload transport formulae like equation fail when normalΘ2normalΘtr (Meyer‐Peter & Müller, ; Recking et al, ) and why one should therefore only use data representing bulk transport when testing such relations (Bunte & Abt, ; Shih & Diplas, ; Singh et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…One mechanism is the cumulative effect of successive particle-bed impacts, which causes a fluctuation motion of bed surface particles that makes them more susceptible for entrainment in a continuous rebound state. Note that recent numerical and experimental studies indicate that impact entrainment dominates direct fluid entrainment in turbulent bedload transport [Vowinckel et al, 2016;Pähtz and Durán, 2017;Lee and Jerolmack, 2018]. 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation does not account for the influence of particle impacts, which can cause direct sediment entrainment as well as loosen a given grain (e.g., Ancey, ; Lee & Jerolmack, ; Pähtz & Durán, ; Vowinckel et al, ), thereby decreasing its resisting force and making it easier to move. Many studies have also demonstrated that drag and lift force fluctuations are actually responsible for particle entrainment (e.g., Diplas et al, ; Leary & Schmeeckle, ; Schmeeckle et al, ; Valyrakis et al, ) and that these fluctuations in lift and drag forces vary with p (Schmeeckle et al, ).…”
Section: Discussionmentioning
confidence: 99%